Evaluation of human resources administration systems: Chiavenato model in productive organizations of Manabi, Ecuador - Mendoza-Zambrano, Mariuxi; Villafuerte-Holguín, Jhonny Saulo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This work aims to analyze the development of Ecuadorian human talent, according to the postulates of the Chiavenato Model. From the systemic approach, eleven public and private organizations were explored, strategic for the socioeconomic development of the province of Manabí. The following research techniques were used: checklist, semi-structured interview and contextualized observation, during the 2018-2020 period. As results, an analysis of ten processes carried out in the management of human talent and their implications regarding technological advances, equality between women and men, professional development and personal fulfillment is presented. It is concluded that, in the organizations studied, there is a tendency to limit talent management to the administrative role in charge of recruitment, remuneration, social benefits and occupational health; leaving a significant gap in areas such as organizational development, career planning, and people's job happiness.